2008
DOI: 10.1359/jbmr.080509
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Linkage Disequilibrium Block in Chromosome 1q Associated With BMD in Premenopausal White Women

Abstract: ABSTRACT:Osteoporosis is a complex disease with both genetic and environmental risk factors. A major determinant of osteoporotic fractures is peak BMD obtained during young adulthood. We previously reported linkage of chromosome 1q (LOD ‫ס‬ 4.3) with variation in spinal areal BMD in healthy premenopausal white women. In this study, we used a two-stage genotyping approach to identify genes in the linked region that contributed to the variation of femoral neck and lumbar spine areal BMD. In the first stage, 654 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…We previously reported that a linkage disequilibrium block on chromosome 1q is associated with BMD (Ichikawa et al , 2008). This region was initially identified through linkage analysis using spine BMD as the phenotype of interest (Econs et al , 2004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that a linkage disequilibrium block on chromosome 1q is associated with BMD (Ichikawa et al , 2008). This region was initially identified through linkage analysis using spine BMD as the phenotype of interest (Econs et al , 2004).…”
Section: Resultsmentioning
confidence: 99%
“…We applied regSNPs to prioritize regulatory SNPs within the genetic regions known to be associated with BMD from a list of candidate SNPs in the HapMap database. We previously reported that a linkage disequilibrium block on chromosome 1q is associated with BMD ( Ichikawa et al , 2008 ). This region was initially identified through linkage analysis using spine BMD as the phenotype of interest ( Econs et al , 2004 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ioannidis and colleagues have reported a meta-analysis of nine genome-wide association studies limited to women that found several chromosomal regions, including 1p13.3-1q23.3, with significant BMD association. (7) In two additional studies, Schaffer and colleagues (8) found significant association of BMD with 1q23 in young 25-to 45-year-old ORIGINAL ARTICLE J JBMR Mexican Americans, and Ichikawa and colleagues (9) reported a significant association of BMD with a haplotype block containing 11 genes on 1q in premenopausal white women, but the specific gene was not identified.…”
Section: Introductionmentioning
confidence: 99%
“…Some QTLs for BMD have been replicated in large consortia (21); however, most of the variance in the heritability of the osteoporosis remains unaccounted for (71) and the identification of key candidate genes even within the replicated regions is challenging. Ongoing work continues to resolve the QTLs to a gene responsible for the signal, both in humans (20) and animal models (12). Positional candidates in the QTL may include many genes known to affect bone growth or maintenance and genes that have not yet been associated with bone mineralization, structure, or body size but potentially influence these traits.…”
Section: Discussionmentioning
confidence: 99%